Ionic Liquids for Extraction of P-Carotene: Modeling and Experimental Approaches - RAJABI, MANSOURE SADAT (2016)
~-carotene, an important bio-molecule with highly unsaturated heavy structure (C4oHs6) is available in plenty of natural products. This hydrocarbon with noticeable antioxidant is a valuable compound in food and pharmaceutical industries. ~-carotene has been extracted from different sources using several techniques including super critical fluid extraction, ultrasound assisted extraction and traditional solvent extraction.